125k views
3 votes
The equation a = StartFraction one-half EndFraction left-parenthesis b 1 plus b 1 right-parenthesis.(b1 + b2)h can be used to determine the area, a, of a trapezoid with height, h, and base lengths, b1 and b2. Which are equivalent equations? Check all that apply.a.
(2a)/(h) - b_2 = b_1

b.
(a)/(2h) - b_2 = b_1
c.
(2a - b_2)/(h) = b_1
d.
(2a)/(b_1 + b_2) = h
e.
(a)/(2(b_1 + b_1)) = h

User Maazza
by
4.7k points

2 Answers

2 votes

Answer:

i know this was months ago but ill do this to help other people :)

Explanation:

The equation a = StartFraction one-half EndFraction left-parenthesis b 1 plus b 1 right-example-1
User Seon
by
5.2k points
0 votes

The equivalent equations to the trapezoid area formula
\( a = (1)/(2) (b_1 + b_2)h \) are
\( (2a)/(h) - b_2 = b_1 \) and
\( (2a)/(b_1 + b_2) = h \), expressing the relationship between area, height, and base lengths.

The trapezoid area formula
\( a = (1)/(2) (b_1 + b_2)h \) describes the area a in terms of height h, and base lengths
\(b_1\) and \(b_2\). The equivalent equations are:

a.
\( (2a)/(h) - b_2 = b_1 \) - Represents a valid rearrangement of the formula.

d.
\( (2a)/(b_1 + b_2) = h \) - Expresses height h in terms of area
\(a\), \(b_1\), and \(b_2\).

These equations are equivalent to the given trapezoid area formula, providing alternate ways to express the relationship between area, height, and base lengths.

User Amir Gorji
by
4.3k points